Hegemoni Patriarki Publik Terhadap Tokoh Perempuan dalam Novel "Hanauzumi" Karya Junichi Watanabe - Retno Putri Utami; Endry Boeriswati; Zuriyati Zuriyati (Indonesian Language Education and Literature, 2018)
This research examines forms of the hegemony of a patriarchal ideology in the public sphere towards women, especially female figures in the Hanauzumi novel by Junichi Watanabe. Hanauzumi's novel tells the story of Japanese women in the 19th century who often experience gender discrimination. The culture and tradition of Japanese society that adheres to and glorifies patriarchal ideology have limited the scope of women in the public sphere. This condition arises because of the leadership and power of men who get an agreement from a group that is hegemony, namely the women themselves. The method used in this study is a qualitative method with content analysis techniques. The data that is the object of this research are narratives and dialogues that identify forms of public patriarchal hegemony towards female leaders. Based on the results of the analysis, it was found that the form of public patriarchal hegemony in female characters in Hanauzumi's novels was the separation of work positions, wage differentiation, absence of women in important positions in the country, limited rights of women in law and politics, cases of physical and mental violence by men, women's limited education and oppression of women in the mass media.Â Penelitian ini bertujuan mengkaji bentuk-bentuk hegemoni suatu ideologi patriarki di bidang publik terhadap perempuan, khususnya tokoh perempuan dalam novel â€œHanauzumiâ€ karya Junichi Watanabe. Novel â€œHanauzumiâ€ menceritakan kisah kaum perempuan Jepang di abad 19 yang sering mengalami diskriminasi gender. Budaya dan tradisi masyarakat Jepang yang menganut dan mengagungkan ideologi patriarki mengakibatkan ruang lingkup kaum perempuan di ranah publik menjadi terbatas. Kondisi ini muncul karena adanya kepemimpinan dan kekuasaan kaum laki-laki yang mendapat kesepakatan dari kelompok yang dihegemoni, yaitu kaum perempuan itu sendiri. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan teknik analisis isi. Data yang menjadi objek penelitian ini adalah narasi dan dialog yang mengidentifikasikan bentuk-bentuk hegemoni patriarki publik terhadap tokoh perempuan. Berdasarkan hasil analisis, ditemukan bahwa bentuk hegemoni patriarki publik pada tokoh perempuan dalam novel â€œHanauzumiâ€ berupa pemisahan posisi kerja, pembedaan upah, ketidakhadiran perempuan dalam posisi penting di negara, terbatasnya hak perempuan dalam bidang hukum dan politik, kasus kekerasan fisik dan mental oleh laki-laki, terbatasnya perempuan dalam pendidikan dan tertindasnya kaum perempuan dalam media massa.